Comparative Genomics Reveals Ecological and Evolutionary Insights into Sponge-Associated Thaumarchaeota - Zhang, Shan (mSystems, 2019)
Thaumarchaeota are frequently reported to associate with marine sponges (phylum Porifera); however, little is known about the features that distinguish them from their free-living thaumarchaeal counterparts. In this study, thaumarchaeal metagenome-assembled genomes (MAGs) were reconstructed from metagenomic data sets derived from the marine sponges Hexadella detritifera, Hexadella cf. detritifera, and Stylissa flabelliformis. Phylogenetic and taxonomic analyses revealed that the three thaumarchaeal MAGs represent two new species within the genus Nitrosopumilus and one novel genus, for which we propose the names “Candidatus (U)Nitrosopumilus hexadellus,” “Candidatus (U)Nitrosopumilus detritiferus,” and “Candidatus (U)Cenporiarchaeum stylissum” (the U superscript indicates that the taxon is uncultured). Comparison of these genomes to data from the Sponge Earth Microbiome Project revealed that “Ca. (U)Cenporiarchaeum stylissum” has been exclusively detected in sponges and can hence be classified as a specialist, while “Ca. (U)Nitrosopumilus detritiferus” and “Ca. (U)Nitrosopumilus hexadellus” are also detected outside the sponge holobiont and likely lead a generalist lifestyle. Comparison of the sponge-associated MAGs to genomes of free-living Thaumarchaeota revealed signatures that indicate functional features of a sponge-associated lifestyle, and these features were related to nutrient transport and metabolism, restriction-modification, defense mechanisms, and host interactions. Each species exhibited distinct functional traits, suggesting that they have reached different stages of evolutionary adaptation and/or occupy distinct ecological niches within their sponge hosts. Our study therefore offers new evolutionary and ecological insights into the symbiosis between sponges and their thaumarchaeal symbionts. IMPORTANCE Sponges represent ecologically important models to understand the evolution of symbiotic interactions of metazoans with microbial symbionts. Thaumarchaeota are commonly found in sponges, but their potential adaptations to a host-associated lifestyle are largely unknown. Here, we present three novel sponge-associated thaumarchaeal species and compare their genomic and predicted functional features with those of closely related free-living counterparts. We found different degrees of specialization of these thaumarchaeal species to the sponge environment that is reflected in their host distribution and their predicted molecular and metabolic properties. Our results indicate that Thaumarchaeota may have reached different stages of evolutionary adaptation in their symbiosis with sponges.